Akumulasi Timbal (Pb) dan Kadmium (Cd) pada Ikan Nila (Oreochromis niloticus) Budidaya Keramba Sungai serta Kaitannya dengan Kualitas Perairan di Desa Lingsar, Lombok Barat, Nusa Tenggara Barat - Feby Fabiola; Muammar Zulfie Ali; Baiq Friska Mutiasari (Lembaga Publikasi Ilmiah Nusantara, 2026)
Heavy metal contamination in aquaculture waters can degrade environmental quality and pose a threat to food safety through bioaccumulation in aquatic organisms. This study aimed to investigate the accumulation of lead (Pb) and cadmium (Cd) in water and the muscle tissue of Nile tilapia (Oreochromis niloticus) cultured in floating net cages along the Lingsar River, West Lombok Regency, West Nusa Tenggara, Indonesia, and to evaluate its relationship with water quality parameters. A field survey was conducted using a purposive sampling approach at three sampling stations representing the upstream, midstream, and downstream sections of the river. Water quality parameters, including temperature, pH, dissolved oxygen (DO), and total dissolved solids (TDS), were measured, while Pb and Cd concentrations were determined using Atomic Absorption Spectrophotometry (AAS). The results indicated that the water quality remained suitable for Nile tilapia culture, with temperature ranging from 26.8 to 28.1°C, pH from 6.91 to 7.42, DO from 5.67 to 6.82 mg/L, and TDS from 118 to 156 mg/L. Lead and cadmium concentrations in water ranged from 0.006 to 0.013 mg/L and 0.001 to 0.003 mg/L, respectively, whereas their concentrations in fish muscle tissue ranged from 0.12 to 0.26 mg/kg and 0.021 to 0.047 mg/kg, respectively. Both metals exhibited an increasing accumulation trend from the upstream to the downstream sections of the river. Decreases in pH and dissolved oxygen were associated with increased Pb and Cd accumulation in fish muscle tissue. Although the concentrations of both metals remained below the maximum permissible limits for fishery products, their presence indicates the need for continuous water quality monitoring and effective management of pollution sources to ensure environmental sustainability and food safety.